Clinical trials in children - Joseph, Pathma D.; Craig, Jonathan C.; Caldwell, Patrina H.Y. (British journal of clinical pharmacology, 2015)
Safety and efficacy data on many medicines used in children are surprisingly scarce. As a result children are sometimes given ineffective medicines or medicines with unknown harmful side effects. Better and more relevant clinical trials in children are needed to increase our knowledge of the effects of medicines and to prevent the delayed or non‐use of beneficial therapies. Clinical trials provide reliable evidence of treatment effects by rigorous controlled testing of interventions on human subjects. Paediatric trials are more challenging to conduct than trials in adults because of the paucity of funding, uniqueness of children and particular ethical concerns. Although current regulations and initiatives are improving the scope, quantity and quality of trials in children, there are still deficiencies that need to be addressed to accelerate radically equitable access to evidence‐based therapies in children.